2015
DOI: 10.1108/jes-04-2014-0065
|View full text |Cite
|
Sign up to set email alerts
|

An error-correction modeling of US consumer spending: are there asymmetries?

Abstract: Purpose -The purpose of this paper is to investigate four possible asymmetries in US aggregate consumption and its major components (durables, non-durables, and services) for the period 1990-2013. Understanding the asymmetric behavior of the components is important since the impact of monetary policy on separate consumer spending categories may differ substantially. Design/methodology/approach -The authors first employ stationarity and cointegration tests to specify and estimate the long-run equilibrium relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(29 citation statements)
references
References 37 publications
(35 reference statements)
2
26
1
Order By: Relevance
“…This result reinforces the ratchet effect described above, but contradicts the psychological negativity bias, according to which people are generally more sensitive to bad news than they are to good news (Rozin and Royzman, ). While empirical research has shown that psychological negativity bias holds for aggregate consumption (Nguyen and Claus, ; Baghestani and Kherfi, ), our findings suggest otherwise for consumer spending on gasoline. This may be due to the lack of close substitutes for gasoline.…”
Section: Data Methodology and Empirical Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…This result reinforces the ratchet effect described above, but contradicts the psychological negativity bias, according to which people are generally more sensitive to bad news than they are to good news (Rozin and Royzman, ). While empirical research has shown that psychological negativity bias holds for aggregate consumption (Nguyen and Claus, ; Baghestani and Kherfi, ), our findings suggest otherwise for consumer spending on gasoline. This may be due to the lack of close substitutes for gasoline.…”
Section: Data Methodology and Empirical Resultscontrasting
confidence: 85%
“…Consistent with this notion, Nguyen and Claus (2013) show that Australian aggregate consumption asymmetrically responds to changes in consumer sentiment. 1 Baghestani and Kherfi (2015) provide similar findings for US aggregate consumption and its major components. For instance, they show that US consumers reduce spending on durable goods, nondurable goods and services in response to a drop in consumer sentiment, but do not adjust such spending when sentiment improves.…”
Section: Related Literaturesupporting
confidence: 55%
“…However, when we consider the short-run estimates from the nonlinear models (NL-ARDL) either the ΔPOS or ΔNEG variable carry at least one significant coefficient in all models. These Durmaz (2015), Baghestani and Kherfi (2015), Pal and Mitra (2016), Al-Shayeb and Hatemi-J. (2016), Lima et al (2016), Nusair (2017), Aftab et al (2017), andGregoriou (2017).…”
Section: Resultsmentioning
confidence: 98%
“…Table 1 reports the results. For more on the application of these methods see (Delatte and Lopez-Villavicencio 2012;Bahmani-Oskooee and Fariditavana 2015;Bahmani-Oskooee and Sujata 2015;Durmaz 2015;Baghestani and Kherfi 2015;Pal and Mitra 2016;Al-Shayeb and Hatemi-J 2016;Lima et al 2016;Nusair 2017;Aftab et al 2017;Gregoriou 2017 From the short-run estimates of the linear models reported in Panel A, we gather that policy uncertainty measure has a significant effect on oil prices in the cases of Canada, Europe, Japan, Russia, South Korea, and the U.S. In all the cases, the effects are adverse, implying that increased uncertainty in any of these countries has adverse effects on oil prices.…”
Section: Resultsmentioning
confidence: 99%